Social relations and environmental influence as a determinant of customer capital - Wieslawa Caputa (Institute of Economic Research (IER), 2014)
In the article there is an influence presented of feedback and recommendations provided by the customers on customer purchase behavior along with the benefits resulting from using the customer feedback potential in the process of company value creation. On the basis of survey research conducted on the beer market in Poland it was indicated that customer feedback and recommendations have a significant influence on purchase behavior and allow cost reduction of customer communication. In the results of the analysis there were statistical methods used, including focus analysis, ANOVA test and factor analysis.
Keywords: A11; D11; D12; 330; customer; customer capital; company value; business relationships